Capacity development among academic trainees in community-based primary health care research: The Aging, Community and Health Research Unit Experience. (2019) - Ganann, Rebecca; Peacock, Shelley; Garnett, Anna; Northwood, Melissa; Hyde, Ashley; Bookey-Bassett, Sue; Kennedy, Laurie; Markle-Reid, Maureen; Ploeg, Jenny; Valaitis, Ruta
Abstract: Health care system capacity and sustainability to address the needs of an aging population are a challenge worldwide. An aging population has brought attention to the limitations associated with existing health systems, specifically the heavy emphasis on costly acute care and insufficient investments in comprehensive primary health care (PHC). Health system reform demands capacity building of academic trainees in PHC research to meet this challenge. The Aging, Community and Health Research Unit at McMaster University has purposefully employed a capacity building model for interdisciplinary trainee development. This paper will describe the processes and outcomes of the model, outlining how the provision of funding, mentorship, and a unique learning environment enables capacity building in networking, collaboration, leadership development, and knowledge mobilization among its trainees. The reciprocal advancement of the research unit through the knowledge and productivity of trainees will also be detailed.